2018
DOI: 10.1016/j.fuel.2018.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of NO and Hg0 using Fe and Co co-doped Mn-Ce/TiO2 catalysts

Abstract: Fe and Co co-doped Mn-Ce/TiO2 (MCT) catalysts were investigated for the simultaneous removal of nitric oxide (NO) and elemental mercury (Hg 0 ) at reaction temperature lower than 200 °C. The catalysts were characterized by Brunauer-Emmett-Teller (BET), temperature program reduction (TPR), scanning electron microscope (SEM), x-ray diffraction (XRD) and x-ray photoelectron spectroscopy (XPS) analysis.The experimental results showed that the co-doped 2Fe4Co-MCT catalyst exhibited better performance for the simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 69 publications
3
40
0
Order By: Relevance
“…It is an attractive and promising denitrification technology. Therefore, it is urgent to study CO-SCR technology [187][188][189]. Besides, precious metals are expensive, have limited reserves and have poor high temperature performance.…”
Section: Co-scrmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an attractive and promising denitrification technology. Therefore, it is urgent to study CO-SCR technology [187][188][189]. Besides, precious metals are expensive, have limited reserves and have poor high temperature performance.…”
Section: Co-scrmentioning
confidence: 99%
“…In order to further explore the performance of CO-SCR denitrification, Shen et al [187] found that the operating temperature window moved towards low temperature after Fe co-doping with Mn-Ce/TiO 2 . Yang et al [193] studied the application of gas sensor in denitrification.Chen et al [194] studied the CO+NO reaction on Pd/Al 2 O 3 and Pd/CeZrO 2 catalysts.…”
Section: Co-scrmentioning
confidence: 99%
“…As shown in Figure , the CeO 2 ‐TiO 2 sorbent can easily dissociate H 2 S into active S. Thereby adsorbed Hg 0 can react with S, leading to the formation of HgS. The other advantage of CeO 2 is that the surface oxygen can react with other flue gases (HCl and NH 3 ) and the products can enhance the Hg 0 removal process by interacting with Hg and forming oxidized mercury products …”
Section: Hg0 Removalmentioning
confidence: 99%
“…The other advantage of CeO 2 is that the surface oxygen can react with other flue gases (HCl and NH 3 ) and the products can enhance the Hg 0 removal process by interacting with Hg and forming oxidized mercury products. [73,77,92,111] Several researchers have investigated the positive effect of SO 2 on Hg 0 removal using CeO 2 -TiO 2 -based catalysts. [79,95] Zhang et al [79] proposed that the increased Hg 0 removal over CeO 2 -TiO 2 follows the Langmuir-Hinshelwood mechanism, where the adsorbed Hg 0 (Equation 9) reacts with the surface oxygen of CeO 2 to form HgO (Equation 10).…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…The metal oxides loaded on AC can also improve denitrification activity significantly. The oxides of transition metals, such as V, Mn, Fe, Cr, and Ni, impregnated on AC can efficiently promote the removal of NO . The transition metal oxides can highly disperse onto an inert carrier to remove NO as active components and play a dominant role in NO oxidation .…”
Section: Introductionmentioning
confidence: 99%